Development and Validation of a Short Form of the German Self-Consciousness Scale for the General Population - Kyla Brophy; Matthew Emery; Adina Coroiu; Cornelia Albani; Elmar Braehler; Annett Körner (European Journal of Psychology Open)
Abstract: Background: The German translation of the Self-Consciousness Scale (Fragebogen zur Erfassung dispositionaler Selbstaufmerksamkeit [SAM]) is a 27-item, self-report measure assessing self-consciousness. Previous studies showed a poor fit for the proposed two-factor structure, assessing private and public self-consciousness. We assessed the factor structure of the German version to develop and validate a short form, aiming to improve model fit and provide a brief version for use in research and clinical practice. Method: Participants were 2,326 adults representative of the German general population, divided randomly into two comparable samples: Sample A and Sample B. We used confirmatory factor analysis (CFA) with Sample A to inform item selection; we used Sample B to evaluate the proposed short form, examining structural validity, measurement invariance, and convergent validity with measures assessing quality of life, well-being, neuroticism, and stress. Results: The results support a two-factor hierarchical model for the 12-item short form, demonstrating full measurement invariance across gender, age, and education level. We found positive correlations between self-consciousness, quality of life, well-being, and chronic stress. Discussion: The results support the use of the SAM-SF to provide a total score as well as subscale scores for private and public self-consciousness.